Nanowire reinforced hydrogel raw material composition, nanowire reinforced hydrogel, and preparation method and application of nanowire reinforced hydrogel

By introducing components such as potassium or sodium-based oxylate nanowires with reduced low-cost transition metal ion exchanged in the hydrogel, a sodium titanate nanowire reinforced hydrogel with dual network structure was prepared, which solved the problem of insufficient elasticity and toughness of the existing hydrogels, and achieved a hydrogel with high tensile, high toughness and good elasticity.

CN119505289AActive Publication Date: 2025-02-25SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411852915.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The artificial ionic skin of the existing hydrogel system is poor in elasticity and toughness, making it difficult to maintain its original shape and function during repeated deformation.

Method used

Sodium titanate nanowire reinforced hydrogel with dual network structure is prepared using potassium or sodium-based oxylate nanowires exchanged with reduced low-cost transition metal ion, water-soluble polymer, acrylamide and initiators.

Benefits of technology

The hydrogel is achieved with high tensile properties, high toughness and good elasticity, and can maintain its original shape and restore its original structure during repeated deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505289A_ABST
    Figure CN119505289A_ABST
Patent Text Reader

Abstract

The invention discloses a nanowire reinforced hydrogel raw material composition, nanowire reinforced hydrogel and a preparation method and application thereof. The raw material composition comprises potassium-based and / or sodium-based oxysalt nanowires subjected to ion exchange with reducing low-valence transition metal, a water-soluble high-molecular compound, acrylamide and an initiator, the mass ratio of the potassium-based and / or sodium-based oxysalt nanowire subjected to ion exchange of the reducing low-valence transition metal to the water-soluble high-molecular compound is 1: (10-300), the mass ratio of the water-soluble high-molecular compound to the acrylamide is 1: (0.5-20), and the mass ratio of the acrylamide to the initiator is 1: (0.001-0.1). The nanowire reinforced hydrogel prepared by the invention has high stretchability, high toughness and good elasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a nanowire-enhanced hydrogel raw material composition, a nanowire-enhanced hydrogel, and a preparation method and application thereof. Background Art

[0002] Inspired by the ion conduction properties and sensory functions of the skin, artificial ion skin (hydrogel, ion gel, ion elastomer, etc.) based on ion conduction can realize multiple sensing functions such as temperature, pressure and strain. Among them, hydrogel is mainly composed of a hydrophilic polymer three-dimensional network structure, which can swell rapidly in water. It has multiple characteristics such as high water content, good flexibility and strong permeability. At the same time, the unique network structure of the hydrogel material system also makes it have high ion conductivity and excellent biocompatibility. However, the skin not only has ion conduction and sensory functions, but also needs to maintain its original shape and function during repeated deformation to restore its original mechanical properties and sensory ability. Therefore, the artificial ion skin of the hydrogel system needs to further develop elasticity to improve its function.

[0003] The elasticity of the hydrogel reflects the ability of the polymer network to recover its original shape. According to the reversibility of the recovery of the polymer network, it can be divided into elastic deformation and plastic deformation. Elastic deformation refers to the part of the polymer network that can recover to its original shape during the deformation process, while plastic deformation refers to the part that cannot recover to its original shape. Hydrogels often fix the polymer network by chemically cross-linking polymer chains so that only the relative position changes during the deformation process, thereby improving elastic deformation. However, chemically cross-linked hydrogels have poor toughness, are easy to break, and are difficult to resist the expansion of cracks, which affects the long-term use of electronic skin. Therefore, it is particularly important to develop a hydrogel that is both elastic and highly tough. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the defects of poor elasticity and toughness of artificial ionic skin of hydrogel system in the prior art, and provide a nanowire-enhanced hydrogel raw material composition, nanowire-enhanced hydrogel and preparation method and application. The nanowire-enhanced hydrogel prepared by the present invention has high tensile properties, high toughness and good elasticity.

[0005] The present invention uses acrylamide, a water-soluble high molecular polymer, an initiator and a potassium-based or sodium-based oxygen-containing salt nanowire exchanged with a reducing low-valent transition metal ion to prepare a sodium titanate nanowire-enhanced hydrogel with a double network structure, wherein the polyacrylamide formed by the outward polymerization of acrylamide along the ion exchange nanowire in the presence of a reducing low-valent transition metal ion serves as the first heavy hydrogen bond network (during the reaction, the low-valent transition metal ion is oxidized to a high-valent state), and the water-soluble high molecular polymer serves as the second heavy network. The water-soluble high molecular polymer forms a coordination bond and a hydrogen bond network with the ion exchange nanowire and the polyacrylamide, respectively, and is anchored around the nanowire to form a polymer network with the nanowire as a crosslinking point. The double network composed of ion exchange nanowires as anchor points mimics the intermuscular spine structure in the body of fish, so that the peripheral polymer chains always only change their relative positions during repeated deformations, and maintain elastic deformation.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a nanowire-enhanced hydrogel raw material composition, which comprises the following components: potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, a water-soluble polymer compound, acrylamide and an initiator;

[0008] Among them, the mass ratio of the potassium-based and / or sodium-based oxygen-containing salt nanowires exchanged with reducing low-valent transition metal ions to the water-soluble polymer compound is 1:(10-300), the mass ratio of the water-soluble polymer compound to the acrylamide is 1:(0.5-20), and the mass ratio of the acrylamide to the initiator is 1:(0.001-0.1).

[0009] In the present invention, the reducing low-valent transition metal ion is preferably Sn. 2+ , Cu + , Fe 2+ , Mn 2+ 、Ti 3+ 、Ru 3+ , Nb 3+ 、 3+ and V 3+ One or more of .

[0010] In the present invention, in the potassium and / or sodium oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, the molar ratio of "potassium and / or sodium oxyacid salt nanowires" to the reducing low-valent transition metal ions can be 1:(5-100), preferably 1:(10-80).

[0011] In the present invention, according to the common practice in the art, the potassium-based and / or sodium-based oxoacid salt nanowires are generally layered materials.

[0012] In the present invention, the potassium-based and / or sodium-based oxyacid salt is preferably a titanate or a manganate, such as Na2Ti3O7, Na2Ti6O 13 Or Na 0.44 M n O2.

[0013] In a specific embodiment, the potassium-based and / or sodium-based oxoacid salt nanowires are Na2Ti3O7 nanowires.

[0014] In the present invention, the preparation method of the potassium and / or sodium oxyacid salt nanowires exchanged with reducing low-valent transition metal ions preferably includes the following steps: mixing the "potassium and / or sodium oxyacid salt nanowires" and a reducing low-valent transition metal salt solution to achieve ion exchange; wherein the molar ratio of the "potassium and / or sodium oxyacid salt nanowires" to the reducing low-valent transition metal salt is 1:(5-100).

[0015] The diameter of the "potassium-based and / or sodium-based oxo acid salt nanowire" may be 0.01-1 μm. The length of the "potassium-based and / or sodium-based oxo acid salt nanowire" may be 0.1-1000 μm.

[0016] Among them, the preparation method of the "potassium-based and / or sodium-based oxygen-containing salt nanowires" can be conventional in the art, and preferably includes the following steps: a mixed solution containing "titanium dioxide or manganese oxide" and a strong base is subjected to a hydrothermal reaction at 170-210°C for 18-96h, and then washed and dried.

[0017] The strong base may be sodium hydroxide and / or potassium hydroxide. In the mixed solution, the concentration of the strong base may be 5-12M, for example, 10M. The mass ratio of the "titanium dioxide or manganese oxide" to the strong base may be 1:(100-140), for example, 1:120. The temperature of the hydrothermal reaction may be 180-200°C, for example, 190°C. The time of the hydrothermal reaction may be 18-30h, for example, 24h.

[0018] Among them, the reducing low-valent transition metal salt is preferably one or more of hydrochlorides, sulfates and nitrates of reducing low-valent transition metals, for example, one or more of stannous chloride, stannous sulfate, cuprous sulfate, cuprous chloride, ferrous sulfate and ferrous chloride.

[0019] The concentration of the reducing low-valent transition metal salt solution may be (0.05-1) g / mL, preferably (0.05-0.5) g / mL, such as 0.08 g / mL, 0.1 g / mL, 0.12 g / mL or 0.2 g / mL.

[0020] Wherein, the molar ratio of the "potassium-based and / or sodium-based oxygen-containing acid salt nanowires" to the reductive low-valent transition metal salt is preferably 1:(10-80), such as 1:15.9, 1:21.3, 1:27.1 or 1:71.7.

[0021] The mixing method may be conventional in the art, such as stirring or ultrasound. The mixing time may be 10 min-6 h, preferably 0.5 h-2 h, such as 0.5 h, 1 h, 1.5 h or 2 h.

[0022] According to the common practice in the art, after the mixing is completed, filtering and washing, such as suction filtration, are generally required.

[0023] In the preparation process of the potassium and / or sodium oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, the metal cations in the reducing low-valent transition metal salt are exchanged with the cations in the "potassium and / or sodium oxyacid salt nanowires". The higher the concentration of the reducing low-valent transition metal salt solution and the longer the mixing time, the higher the content of transition metal ions in the potassium and / or sodium oxyacid salt nanowires exchanged with reducing low-valent transition metal ions; the molar ratio of the "potassium or sodium oxyacid salt nanowires" and the reducing low-valent transition metal salt affects the distribution ratio of the reducing low-valent transition metal cations in the nanowires.

[0024] In the present invention, the water-soluble polymer compound can be a carboxyl-containing polymer, preferably one or more of sodium alginate, polyacrylic acid and carboxymethyl cellulose. The carboxyl group in the water-soluble polymer compound forms a coordination bond with the cation in the potassium-based and / or sodium-based oxoacid salt nanowires exchanged with the reducing low-valent transition metal ions, which helps to disperse the nanowires and strengthen the hydrogel.

[0025] In the present invention, the initiator may be a water-soluble free radical initiator, preferably one or more of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline.

[0026] In the present invention, the mass ratio of the potassium and / or sodium oxygen-containing salt nanowires exchanged with reducing low-valent transition metal ions and the water-soluble polymer compound is preferably 1:(10-200), for example, 1:40, 1:50, 1:55.6, 1:80, 1:100, 1:143, 1:200, and more preferably 1:(20-50).

[0027] In the present invention, the mass ratio of the water-soluble polymer compound to the acrylamide is preferably 1:(1-10), such as 1:1, 1:2.5, 1:4 or 1:8.

[0028] In the present invention, the mass ratio of the acrylamide to the initiator is preferably 1:(0.01-0.05), such as 1:0.02, 1:0.025 or 1:0.0375.

[0029] In the present invention, the nanowire-enhanced hydrogel raw material composition preferably also includes a solvent.

[0030] The solvent may be one or more of deionized water, ethanol, ethylene glycol and glycerol.

[0031] The ratio of the sum of the masses of the potassium and / or sodium oxoacid salt nanowires exchanged with reducing low-valent transition metal ions, the water-soluble polymer compound, the acrylamide and the initiator to the volume of the solvent may be (0.1-2.0) g / mL, preferably (0.2-1.0) g / mL, for example 0.44 g / mL, 0.49 g / mL or 0.68 g / mL.

[0032] In the present invention, the nanowire-enhanced hydrogel raw material composition preferably comprises the following components: potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, a "mixed solution containing a water-soluble polymer compound and acrylamide" and a "solution containing an initiator";

[0033] Among them, the mass ratio of the potassium-based and / or sodium-based oxygen-containing salt nanowires exchanged with reducing low-valent transition metal ions to the water-soluble polymer compound is 1:(10-300), the mass ratio of the water-soluble polymer compound to the acrylamide is 1:(0.5-20), and the mass ratio of the acrylamide to the initiator is 1:(0.001-0.1).

[0034] The solvents in the "mixed solution containing a water-soluble polymer compound and acrylamide" and the "solution containing an initiator" are as described above.

[0035] Wherein, in the "mixed solution containing a water-soluble polymer compound and acrylamide", the concentration of acrylamide may be (0.1-1) g / mL, such as 0.2 g / mL, 0.4 g / mL, 0.5 g / mL or 0.8 g / mL.

[0036] Wherein, in the “solution containing an initiator”, the concentration of the initiator may be (0.1-1) g / mL, such as 0.2 g / mL, 0.25 g / mL or 0.3 g / mL.

[0037] The present invention also provides a nanowire-enhanced hydrogel, which is prepared by mixing the nanowire-enhanced hydrogel raw material composition as described above.

[0038] In the present invention, the nanowire-enhanced hydrogel can be prepared into hydrogel products with different morphologies and sizes according to actual application requirements, for example, into a hydrogel film.

[0039] In the present invention, the breaking length of the nanowire-enhanced hydrogel can be 500%-2500%.

[0040] In the present invention, the breaking strength of the nanowire-reinforced hydrogel may be 50-300 kPa.

[0041] The present invention also provides a method for preparing the nanowire-enhanced hydrogel, which comprises the following steps:

[0042] Method 1: (1) dissolving the water-soluble polymer compound and the acrylamide in a solvent to prepare a solution A; mixing the potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions with the solution A to prepare a solution B;

[0043] (2) dissolving the initiator in a solvent to obtain a solution C, and then mixing the solution C and the solution B and letting them stand for a period of time;

[0044] Or, method 2: (1) dissolving the water-soluble polymer compound and the acrylamide in a solvent to obtain solution A; dissolving the initiator in a solvent to obtain solution C; mixing the solution A and the solution C to obtain solution D;

[0045] (2) Spraying the potassium-based and / or sodium-based oxygen-containing salt nanowires exchanged with reducing low-valent transition metal ions onto a glass sheet, and then adding the solution D to the surface of the nanowires and letting it stand for a period of time.

[0046] In method 1 and / or method 2, the solvent is as described above.

[0047] In method 1 and / or method 2, the mixing method may be conventional in the art, such as stirring or ultrasound. In method 1, preferably, the solution C is added to the solution B and then mixed.

[0048] In method 1 and / or method 2, there is generally no order in which solution A and solution C are prepared, for example, solution A is prepared first and then solution C, or solution C is prepared first and then solution A, or they are prepared simultaneously.

[0049] In the second method, the potassium-based and / or sodium-based oxo acid salt nanowires exchanged with reducing low-valent transition metal ions are generally prepared into a dispersion for spraying. The solvent in the dispersion can be a conventional volatile solvent in the art, such as ethanol. The concentration of the dispersion generally does not need to be particularly limited, and is preferably (1-10) mg / mL, such as 3 mg / mL, 4.7 mg / mL or 6 mg / mL.

[0050] In method 1 and / or method 2, the standing is generally performed in a mold. The standing time may be 10 min-10 h, preferably 1-5 h, such as 1 h, 2 h or 5 h.

[0051] In method 1 and / or method 2, the standing temperature may be -10°C to 80°C, such as 25°C, 40°C or 60°C, preferably 15-40°C.

[0052] After the solution C and the solution B are mixed, the reducing low-valent transition metal ions on the surface of the nanowires accelerate the decomposition of the initiator into highly active free radicals, which react to generate high-valent transition metal ions, causing the acrylamide monomer to undergo a polymerization reaction at room temperature to obtain a hydrogel that grows epitaxially along the nanowires.

[0053] The amount of the initiator used will affect the polymerization reaction rate and the mechanical properties of the hydrogel. Too much initiator will cause a violent reaction and explosion, while too little will require a longer standing time. The standing time will affect the completeness of the polymerization reaction, while too short a standing time will lead to incomplete polymerization.

[0054] The present invention also provides an application of the nanowire-enhanced hydrogel as described above in the fields of electronic skin, flexible sensors, artificial muscles or gel electrolytes.

[0055] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0056] The reagents and raw materials used in the present invention are commercially available.

[0057] The positive and progressive effects of the present invention are:

[0058] The nanowire-enhanced hydrogel prepared by the present invention has the following advantages:

[0059] (1) Excellent tensile properties: Under the action of the entangled network of polyacrylamide and water-soluble polymer, the hydrogel can obtain high tensile properties through the gradual untangling of the network;

[0060] (2) High toughness: Under the coordination bonds and hydrogen bonds of polyacrylamide and water-soluble polymers, the hydrogel obtains high toughness through the dissipation of reversible physical bonds and hinders the expansion of wound cracks;

[0061] (3) High elasticity: Under the anchoring effect of ion exchange nanowires, the polymer only changes its relative position and can return to its original structure after rebound. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 The following are photos of the polyacrylamide-polyacrylic acid-tin ion exchange hydrogel composition sample prepared in Example 1 (a) before polymerization and (b) after polymerization at room temperature;

[0063] Figure 2 Part (a) is a cryo-electron micrograph of the polyacrylamide-polyacrylic acid-tin ion exchange hydrogel composition sample prepared in Example 1; Figure 2 Part (b) is a cryo-electron micrograph of the polyacrylamide-polyacrylic acid-sodium titanate hydrogel composition sample prepared in Comparative Example 6;

[0064] Figure 3 Part (a) is a white gel in which the polyacrylamide-polyacrylic acid-tin ion exchange hydrogel composition sample prepared in Example 7 is in situ anchored and grown on the ion-exchanged sodium titanate nanowires on a glass slide; Figure 3 Part (b) is a disordered transparent gel grown on sodium titanate nanowires without ion exchange in Comparative Example 5;

[0065] Figure 4 Part (a) is a pressure-stretching curve of the polyacrylamide-polyacrylic acid-tin ion exchange hydrogel composition sample prepared in Example 1 under cyclic stretching of 1 times the initial length; Figure 2 Part (b) is a pressure-stretching curve of the polyacrylamide-polyacrylic acid hydrogel composition sample prepared in Comparative Example 1 under cyclic stretching of 1 times the initial length;

[0066] Figure 5 Part (a) is a pressure-stretching curve of the polyacrylamide-carboxymethyl cellulose-tin ion exchange hydrogel composition sample prepared in Example 2 under cyclic stretching of 1 times the initial length; Figure 3 Part (b) is a pressure-stretching curve of the polyacrylamide-carboxymethyl cellulose hydrogel composition sample prepared in Comparative Example 2 under cyclic stretching of 1 times the initial length;

[0067] Figure 6 The pressure-stretching curves of the polyacrylamide-polyacrylic acid-copper ion exchange hydrogel composition samples prepared in Example 3 and Examples 5-6 and the polyacrylamide-polyacrylic acid sample prepared in Comparative Example 3;

[0068] Figure 7The pressure-stretching curves of the polyacrylamide-polyacrylic acid-copper ion exchange hydrogel composition samples prepared in Example 3, Examples 5-6 and the polyacrylamide-polyacrylic acid sample prepared in Comparative Example 3 under cyclic stretching of 1 times the initial length;

[0069] Figure 8 Part (a) is a pressure-stretching curve of the polyacrylamide-sodium alginate-iron ion exchange hydrogel composition sample prepared in Example 4 and the polyacrylamide-sodium alginate composition sample prepared in Comparative Example 4 under cyclic stretching of 1 times the initial length;

[0070] Fig. 9 This is a current signal diagram of the long-term cyclic operation of the polyacrylamide-sodium alginate-iron ion exchange hydrogel composition sample prepared in Example 4 as a flexible sensor. DETAILED DESCRIPTION

[0071] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0072] The raw material information used in the following examples and comparative examples is shown in Table 1:

[0073] Table 1

[0074]

[0075]

[0076] The preparation method of sodium titanate nanowires used in the following examples is as follows: 12 g of sodium hydroxide is dissolved in 30 mL of deionized water to obtain a sodium hydroxide solution; 0.1 g of titanium dioxide powder is dispersed in a reactor filled with the sodium hydroxide solution, and a hydrothermal reaction is carried out at 190° C. for 24 h. The obtained product is washed with deionized water until it is neutral, and dried to obtain sodium titanate nanowires (with a diameter of 0.5-2 μm and a length of 5-10 μm).

[0077] The size of the mold used in the following Examples 1-6 and Comparative Examples 1-4 and Comparative Example 6 is 75 mm*50 mm*1 mm (length*width*thickness).

[0078] Example 1

[0079] (1) Preparation of ion exchange nanowires: 5 g of stannous chloride was dissolved in 50 g of water to form a stannous chloride solution; 0.5 g of sodium titanate nanowires were immersed in the stannous chloride solution, stirred for 1 hour, and then filtered to obtain stannous ion exchange sodium titanate nanowires;

[0080] (2) Preparation of hydrogel precursor: 2 g of polyacrylic acid and 5 g of acrylamide were dissolved in 10 mL of water, and 14 mg of stannous ion-exchanged sodium titanate nanowires were added to the polyacrylic acid-acrylamide solution and ultrasonically dispersed to obtain a polyacrylic acid-acrylamide-stannous ion-exchanged sodium titanate nanowire dispersion;

[0081] (3) Preparation of sodium titanate nanowire-reinforced hydrogel: 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to prepare an ammonium persulfate solution; the ammonium persulfate solution was added to the polyacrylic acid-acrylamide-stannous ion exchange sodium titanate nanowire dispersion, stirred evenly, poured into a mold and allowed to stand at 25°C for 1 hour to obtain a polyacrylamide-polyacrylic acid-tin ion exchange hydrogel composition sample.

[0082] Example 2

[0083] (1) Preparation of ion exchange nanowires: 4 g of stannous chloride was dissolved in 50 g of water to form a stannous chloride solution; 0.3 g of sodium titanate nanowires was immersed in the stannous chloride solution, stirred for 2 hours, and then filtered to obtain stannous ion exchange sodium titanate nanowires;

[0084] (2) Preparation of hydrogel precursor: 1 g of carboxymethyl cellulose and 4 g of acrylamide were dissolved in 10 mL of water, and 10 mg of stannous ion-exchanged sodium titanate nanowires were added to the carboxymethyl cellulose-acrylamide solution and ultrasonically dispersed to obtain a carboxymethyl cellulose-acrylamide-stannous ion-exchanged sodium titanate nanowire dispersion;

[0085] (3) Preparation of sodium titanate nanowire-reinforced hydrogel: 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to prepare an ammonium persulfate solution; the ammonium persulfate solution was added to the carboxymethyl cellulose-acrylamide-stannous ion exchange sodium titanate nanowire dispersion, stirred evenly, poured into a mold and allowed to stand at 25°C for 2 hours to obtain a polyacrylamide-carboxymethyl cellulose-tin ion exchange hydrogel composition sample.

[0086] Example 3

[0087] (1) Preparation of ion exchange nanowires: 10 g of cuprous sulfate was dissolved in 50 g of water to form a cuprous sulfate solution; 0.5 g of sodium titanate nanowires was immersed in the cuprous sulfate solution, stirred for 0.5 hours, and then filtered to obtain cuprous ion exchange sodium titanate nanowires;

[0088] (2) Preparation of hydrogel precursor: 1 g of polyacrylic acid and 4 g of acrylamide were dissolved in 10 mL of water, and 10 mg of cuprous ion-exchanged sodium titanate nanowires were added to the polyacrylic acid-acrylamide solution and ultrasonically dispersed to obtain a polyacrylic acid-acrylamide-cuprous ion-exchanged sodium titanate nanowire dispersion;

[0089] (3) Preparation of sodium titanate nanowire-reinforced hydrogel: 0.15 g of azobisisobutylamidine hydrochloride was dissolved in 0.5 g of water to prepare an azobisisobutylamidine hydrochloride solution; the azobisisobutylamidine hydrochloride solution was added to the polyacrylic acid-acrylamide-cuprous ion exchange sodium titanate nanowire dispersion, stirred evenly, poured into a mold and allowed to stand at 25°C for 5 hours to obtain a polyacrylamide-polyacrylic acid-cuprous ion exchange hydrogel composition sample.

[0090] Example 4

[0091] (1) Preparation of ion exchange nanowires: 6 g of ferrous chloride was dissolved in 50 g of water to form a ferrous chloride solution; 0.2 g of sodium titanate nanowires was immersed in the ferrous chloride solution, stirred for 1.5 hours, and then filtered to obtain ferrous ion exchange sodium titanate nanowires;

[0092] (2) Preparation of hydrogel precursor: 0.5 g of sodium alginate and 4 g of acrylamide were dissolved in 10 mL of water, and 9 mg of ferrous ion exchange sodium titanate nanowires were added to the sodium alginate-acrylamide solution and ultrasonically dispersed to obtain a sodium alginate-acrylamide-ferrous ion exchange sodium titanate nanowire dispersion;

[0093] (3) Preparation of sodium titanate nanowire-reinforced hydrogel: 0.15 g of potassium persulfate was dissolved in 0.5 g of water to prepare a potassium persulfate solution; the potassium persulfate solution was added to the sodium alginate-acrylamide-ferrous ion exchange sodium titanate nanowire dispersion, stirred evenly, poured into a mold and allowed to stand at 25°C for 2 hours to obtain a polyacrylamide-sodium alginate-ferric ion exchange hydrogel composition sample.

[0094] Example 5

[0095] Compared with Example 3, except that the amount of cuprous ion-exchanged sodium titanate nanowires added in step (2) was adjusted to 5 mg, the other operations and conditions were the same as those in Example 3.

[0096] Example 6

[0097] Compared with Example 3, except that the amount of cuprous ion-exchanged sodium titanate nanowires added in step (2) was adjusted to 25 mg, the other operations and conditions were the same as those in Example 3.

[0098] Example 7

[0099] (1) Preparation of ion exchange nanowires: 5 g of stannous chloride was dissolved in 50 g of water to form a stannous chloride solution; 0.5 g of sodium titanate nanowires were immersed in the stannous chloride solution, stirred for 1 hour, and then filtered to obtain stannous ion exchange sodium titanate nanowires;

[0100] (2) Preparation of sodium titanate nanowire-reinforced hydrogel: 14 mg of stannous ion-exchanged sodium titanate nanowires were dispersed in 3 ml of ethanol, and the nanowire dispersion was sprayed onto a glass sheet using a spray gun and placed in a cylindrical hollow mold (20 mm in diameter and 10 mm in height);

[0101] 2 g of polyacrylic acid and 5 g of acrylamide were dissolved in 10 mL of water to obtain solution A, and 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to obtain solution C. Solution A and solution C were mixed evenly, poured into a cylindrical hollow mold, and allowed to stand at 25°C for 1 hour to grow an orderly white gel.

[0102] Comparative Example 1

[0103] Dissolve 2 g of polyacrylic acid and 5 g of acrylamide in 10 mL of water to obtain solution A;

[0104] 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to prepare solution C; solution C was added to solution A, stirred evenly, poured into a mold and allowed to stand for 0.5 hours under heating conditions at 60° C. to obtain a polyacrylamide-polyacrylic acid hydrogel composition sample.

[0105] Comparative Example 2

[0106] Dissolve 1 g of carboxymethyl cellulose and 4 g of acrylamide in 10 mL of water to obtain solution A;

[0107] 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to prepare solution C; solution C was added to solution A, stirred evenly, poured into a mold and allowed to stand for 0.5 hours under heating conditions at 60° C. to obtain a polyacrylamide-carboxymethyl cellulose hydrogel composition sample.

[0108] Comparative Example 3

[0109] Dissolve 1 g of polyacrylic acid and 4 g of acrylamide in 10 mL of water to obtain solution A;

[0110] 0.15 g of azobisisobutylamidine hydrochloride was dissolved in 0.5 g of water to prepare solution C; solution C was added to solution A, stirred evenly, poured into a mold and allowed to stand for 0.5 hours under heating conditions at 60° C. to obtain a polyacrylamide-polyacrylic acid hydrogel composition sample.

[0111] Comparative Example 4

[0112] Dissolve 0.5 g of sodium alginate and 4 g of acrylamide in 10 mL of water to obtain solution A;

[0113] 0.15 g of potassium persulfate was dissolved in 0.5 g of water to prepare solution C; solution C was added to solution A, stirred evenly, poured into a mold and allowed to stand for 0.5 hours under heating conditions at 60° C. to obtain a polyacrylamide-sodium alginate hydrogel composition sample.

[0114] Comparative Example 5

[0115] 14 mg of sodium titanate nanowires were dispersed in 3 ml of ethanol, and the nanowire dispersion was sprayed onto a glass slide by a spray gun and placed in a cylindrical hollow mold (20 mm in diameter and 10 mm in height);

[0116] 2 g of polyacrylic acid and 5 g of acrylamide were dissolved in 10 mL of water to obtain solution A, and 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to obtain solution B. Solution A and solution B were evenly mixed, poured into a cylindrical hollow mold, and allowed to stand under heating conditions at 60°C for 0.5 hours to grow a disordered transparent gel.

[0117] Comparative Example 6

[0118] (1) Preparation of hydrogel precursor: 2 g of polyacrylic acid and 5 g of acrylamide were dissolved in 10 mL of water, and 14 mg of sodium titanate nanowires were added to the polyacrylic acid-acrylamide solution and ultrasonically dispersed to obtain a polyacrylic acid-acrylamide-sodium titanate nanowire dispersion;

[0119] (2) Preparation of sodium titanate nanowire-reinforced hydrogel: 0.1 g of ammonium persulfate was dissolved in 0.5 g of water to prepare an ammonium persulfate solution; the ammonium persulfate solution was added to the polyacrylic acid-acrylamide-sodium titanate nanowire dispersion, stirred evenly, poured into a mold and allowed to stand at 25°C for 1 hour to obtain a polyacrylamide-polyacrylic acid-sodium titanate hydrogel composition sample.

[0120] Effect Example

[0121] (1) Figure 1 These are photos of the polyacrylamide-polyacrylic acid-tin ion exchange sodium titanate nanowire hydrogel composition sample prepared in Example 1 before and after polymerization at room temperature; after standing at room temperature 25°C for 1 hour, the polyacrylic acid-acrylamide-stannous ion exchange sodium titanate nanowire precursor dispersion is polymerized into a hydrogel.

[0122] Figure 2 Cryo-electron microscopy images of the prepared hydrogel composition samples, (a) shows the in-situ growth of polymer chains on the tin ion exchange nanowires after the reaction, stannous ions can accelerate the generation of free radicals and form a coordination effect with acrylamide, allowing acrylamide to grow on the surface of the nanowires. After rinsing with deionized water, centrifugation and other operations, it is still anchored on the nanowires, but (b) no polymer chains grow on the nanowires without ion exchange at room temperature.

[0123] according to Figure 3 It can be seen that the polyacrylamide-polyacrylic acid-tin ion exchange hydrogel composition sample prepared in Example 7 is a white gel that is in situ anchored and grown on the ion-exchanged nanowires on a glass sheet. After the monomers are aggregated by the coordination effect of the stannous ions, the high-density monomers grow in an orderly manner along the outside of the ion-exchanged nanowires. However, since Comparative Example 5 uses nanowires that have not been ion-exchanged, it cannot be polymerized into a gel at room temperature. Although polymerization occurs after heating at 60°C, a disordered transparent gel is obtained by growing on the non-exchanged nanowires.

[0124] (2) The samples of Examples 1-6 and Comparative Examples 1-4 prepared above (cut into strips with a length*width*thickness of 50 mm*5 mm*1 mm) were subjected to a pressure-tensile test. The relevant test results are shown in Figure 4-Figure 8 According to the test results, when nanowires are not added, the residual strain of the curve is obvious, and the stress is unstable with the increase of the number of cycles. However, when nanowires are added, the residual strain is greatly reduced or even disappears, and the stress is stable.

[0125] (3) The polyacrylamide-polyacrylic acid-copper ion exchange hydrogel composition samples prepared in Example 3, Examples 5-6, and the polyacrylamide-polyacrylic acid sample prepared in Comparative Example 3 (cut into strips with a length*width*thickness of 50 mm*5 mm*1 mm) were subjected to a pressure-tensile test. The test results are shown in Table 2:

[0126] Table 2

[0127]

[0128]

[0129] According to the test data in Table 2, when Cu is added to the reaction system + When sodium titanate nanowires are ion-exchanged, the fracture toughness and stress of the prepared hydrogel samples are significantly improved.

[0130] (4) The polyacrylamide-sodium alginate-iron ion exchange sodium titanate nanowire hydrogel composition sample prepared in Example 4 (pre-cut into strips with a length*width*thickness of 50 mm*5 mm*1 mm) was connected with metal electrodes on the upper and lower surfaces to obtain a flexible sensor. Fig. 9 This is the current signal diagram of the long-term cyclic operation of the flexible sensor. It can be seen from the figure that the resistance change after 2500 cycles under 100% stretching is negligible, and it has cyclic stability and anti-fatigue performance.

[0131] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A nanowire-enhanced hydrogel raw material composition, characterized in that: The method comprises the following components: potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, a water-soluble polymer compound, acrylamide and an initiator; Among them, the mass ratio of the potassium-based and / or sodium-based oxygen-containing salt nanowires exchanged with reducing low-valent transition metal ions to the water-soluble polymer compound is 1:(10-300), the mass ratio of the water-soluble polymer compound to the acrylamide is 1:(0.5-20), and the mass ratio of the acrylamide to the initiator is 1:(0.001-0.1).

2. The nanowire-enhanced hydrogel raw material composition according to claim 1, characterized in that: The reducible low-valent transition metal ion is Sn 2+ , Cu + , Fe 2+ , Mn 2+ 、Ti 3+ 、Ru 3+ , Nb 3+ 、 3+ and V 3+ One or more of; And / or, in the potassium and / or sodium oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, the molar ratio of "potassium and / or sodium oxyacid salt nanowires" to reducing low-valent transition metal ions is 1:(5-100), preferably 1:(10-80).

3. The nanowire-enhanced hydrogel raw material composition according to claim 1, characterized in that: The raw material composition satisfies one or more of the following conditions: (1) The water-soluble polymer compound is a carboxyl-containing polymer, preferably one or more of sodium alginate, polyacrylic acid and carboxymethyl cellulose; (2) The initiator is a water-soluble free radical initiator, preferably one or more of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline; (3) The mass ratio of the potassium and / or sodium oxoacid salt nanowires exchanged with reducing low-valent transition metal ions to the water-soluble polymer compound is 1:(10-200), such as 1:40, 1:50, 1:55.6, 1:80, 1:100, 1:143, 1:200, preferably 1:(20-50); (4) The mass ratio of the water-soluble polymer compound to the acrylamide is 1:(1-10), for example, 1:1, 1:2.5, 1:4 or 1:8; (5) The mass ratio of the acrylamide to the initiator is 1:(0.01-0.05), for example, 1:0.02, 1:0.025 or 1:0.0375.

4. The nanowire-enhanced hydrogel raw material composition according to claim 1, characterized in that: The potassium-based and / or sodium-based oxyacid salt is a titanate or a manganate, such as Na2Ti3O7, Na2Ti6O 13 Or Na 0.44 M n O2; And / or, the preparation method of the potassium and / or sodium oxyacid salt nanowires exchanged with reducing low-valent transition metal ions comprises the following steps: mixing the "potassium and / or sodium oxyacid salt nanowires" and a reducing low-valent transition metal salt solution to achieve ion exchange; wherein the molar ratio of the "potassium and / or sodium oxyacid salt nanowires" to the reducing low-valent transition metal salt is 1:(5-100).

5. The nanowire-enhanced hydrogel raw material composition according to claim 4, characterized in that: The method for preparing the potassium-based and / or sodium-based oxoacid salt nanowires exchanged with reducing low-valent transition metal ions satisfies one or more of the following conditions: (1) The diameter of the "potassium-based and / or sodium-based oxoacid salt nanowires" is 0.01-1 μm; (2) The length of the "potassium-based and / or sodium-based oxoacid salt nanowires" is 0.1-1000 μm; (3) The reducing low-valent transition metal salt is one or more of the hydrochloride, sulfate and nitrate of a reducing low-valent transition metal, for example, one or more of stannous chloride, stannous sulfate, cuprous sulfate, cuprous chloride, ferrous sulfate and ferrous chloride; (4) The concentration of the reducing low-valent transition metal salt solution is (0.05-1) g / mL, preferably (0.05-0.5) g / mL, such as 0.08 g / mL, 0.1 g / mL, 0.12 g / mL or 0.2 g / mL; (5) The molar ratio of the "potassium-based and / or sodium-based oxygen acid salt nanowires" to the reducible low-valent transition metal salt is 1:(10-80), for example, 1:15.9, 1:21.3, 1:27.1 or 1:71.7; (6) The mixing time is 10 min-6 h, preferably 0.5 h-2 h, for example 0.5 h, 1 h, 1.5 h or 2 h.

6. The nanowire-enhanced hydrogel raw material composition according to claim 4, characterized in that: The preparation method of the "potassium-based and / or sodium-based oxyacid salt nanowires" comprises the following steps: subjecting a mixed solution containing "titanium dioxide or manganese oxide" and a strong base to a hydrothermal reaction at 170-210° C. for 18-96 hours, followed by washing and drying; The strong base is preferably sodium hydroxide and / or potassium hydroxide; In the mixed solution, the concentration of the strong base is preferably 5-12M; The mass ratio of the "titanium dioxide or manganese oxide" to the strong base is preferably 1: (100-140).

7. The nanowire-enhanced hydrogel raw material composition according to claim 1, characterized in that: The nanowire-enhanced hydrogel raw material composition also includes a solvent; The solvent is preferably one or more of deionized water, ethanol, ethylene glycol and glycerol; The ratio of the sum of the mass of the potassium and / or sodium oxoacid salt nanowires exchanged with reducing low-valent transition metal ions, the water-soluble polymer compound, the acrylamide and the initiator to the volume of the solvent is preferably (0.1-2.0) g / mL; And / or, the nanowire-enhanced hydrogel raw material composition comprises the following components: potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions, "a mixed solution containing a water-soluble polymer compound and acrylamide" and "a solution containing an initiator"; Wherein, the mass ratio of the potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions to the water-soluble polymer compound is 1:(10-300), the mass ratio of the water-soluble polymer compound to the acrylamide is 1:(0.5-20), and the mass ratio of the acrylamide to the initiator is 1:(0.001-0.1); In the "mixed solution containing a water-soluble polymer compound and acrylamide", the concentration of acrylamide is preferably (0.1-1) g / mL; In the "solution containing an initiator", the concentration of the initiator is preferably (0.1-1) g / mL.

8. A nanowire-enhanced hydrogel, characterized in that: The nanowire-enhanced hydrogel raw material composition is prepared by mixing the nanowire-enhanced hydrogel raw material composition described in any one of claims 1 to 7.

9. A method for preparing a nanowire-enhanced hydrogel as claimed in claim 8, characterized in that: It includes the following steps: Method 1: (1) dissolving the water-soluble polymer compound and the acrylamide in a solvent to prepare a solution A; mixing the potassium-based and / or sodium-based oxyacid salt nanowires exchanged with reducing low-valent transition metal ions with the solution A to prepare a solution B; (2) dissolving the initiator in a solvent to obtain a solution C, and then mixing the solution C and the solution B and letting them stand for a period of time; Or, method 2: (1) dissolving the water-soluble polymer compound and the acrylamide in a solvent to obtain solution A; dissolving the initiator in a solvent to obtain solution C; mixing the solution A and the solution C to obtain solution D; (2) Spraying the potassium-based and / or sodium-based oxygen-containing salt nanowires exchanged with reducing low-valent transition metal ions onto a glass sheet, and then adding the solution D to the surface of the nanowires and letting it stand for a period of time.

10. Use of the nanowire-enhanced hydrogel as claimed in claim 8 in the fields of electronic skin, flexible sensors, artificial muscles or gel electrolytes.

Citation Information

Patent Citations

  • High-conductivity nano composite hydrogel composition and preparation process thereof

    CN117510736A

  • Nanowire enhanced hydrogel composite material and one-pot preparation method thereof

    CN117986636A